Game Ai Using Parametrized Behavior Monitoring - et. al., Raghav Suriyashekar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Game AI with a Non-Player Controlled Bots is the systems that are built into a game. These systems offer competition or objectives that the player must overcome to progress. Although in most situations, these NPCs provide an acceptable level of competition, over time, they become predictable and no longer pose any challenge to the players. Game AIs and NPCs use a basic detection and computational system to perform actions that seem to oppose the players, and these are even lesser of an opposition to players and will lead to loss of worth in the section of the game that would be more enjoyable to those if the opposition would be more challenging.